First Language Attrition and Dominance: Same Same or Different? - Köpke, Barbara; Genevska-Hanke, Dobrinka (Frontiers in Psychology, 2018)
We explore the relationship between first language attrition and language dominance, defined here as the relative availability of each of a bilingual’s languages with respect to language processing. We assume that both processes might represent two stages of one and the same phenomenon (Köpke, 2018; Schmid & Köpke, 2017). While many researchers agree that language dominance changes repeatedly over the lifespan (e.g. Silva-Corvalan & Treffers-Daller, 2015), little is known about the precise time scales involved in dominance shifts and attrition. We investigated such time scales in a longitudinal case study of pronominal subject production by a near-native L2-German (semi-null subject/topic-drop but non-pro-drop) and L1-Bulgarian (pro-drop) bilingual speaker with 15 years of residence in Germany. This speaker’s spontaneous speech showed a significantly higher rate of overt subjects (OS) in her L1 than the controls’ rates when tested in Germany. After a three-week L1 reexposure in Bulgaria, however, attrition effects disappeared and the OS rate fell within the monolinguals’ range (Genevska-Hanke, 2017). The findings of this first investigation were now compared to those of a second investigation five years later, involving data collection in both countries. The results show that after 15 years of immigration, no further attrition was attested and OS production remained monolingual-like for data collection in both language environments. The discussion focuses on the factors that are likely to explain these results. First, these show that attrition and language dominance are highly dependent on immediate language use context and change rapidly when the language environment is modified. Additionally, the data obtained after L1 reexposure illustrate that time scales involved in dominance shift or attrition are much shorter than previously thought. Second, the role of age of acquisition in attrition has repeatedly been acknowledged. The present study demonstrates that attrition of a highly entrenched L1 is a phenomenon affecting language processing only temporarily and that it is likely to regress quickly after reexposure or return to balanced L1 use. The discussion suggests that dominance shift and attrition probably involve similar mechanisms and are influenced by the same external factors, showing that both may be different steps of the same process.